ASME 2007 InterPACK Conference, Volume 1 2007
DOI: 10.1115/ipack2007-33983
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pin-Fin Heat Sinks in Bypass Flow Using Entropy Generation Minimization Method

Abstract: An entropy generation minimization, EGM, method is applied to study the thermodynamic losses caused by heat transfer and pressure drop for the fluid in a cylindrical pin-fin heat sink and bypass flow regions. A general expression for the entropy generation rate is obtained by considering control volumes around heat sink and bypass regions. The conservation equations for mass and energy with the entropy balance are applied in both regions. Inside the heat sink, analytical/empirical correlations are used for hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Chen et al [18] developed an effective method for performing the thermal optimization of fully confined pin fin heat sinks under constraints of pressure drop, mass, and space limitations. Khan et al [19,20] studied the thermodynamic losses caused by heat transfer and pressure drop in cylindrical pin fin heat sinks by applying an entropy generation minimization (EGM) technique, which allows all relevant design parameters for pin-fin heat sinks, including geometric parameters, material properties and flow conditions, to be simultaneously optimized. Chiang et al [21,22] explored the optimal values of designing parameters of a pin fin type heat sink under constrains of mass and space limitation to achieve high thermal performance (or cooling efficiency) by experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [18] developed an effective method for performing the thermal optimization of fully confined pin fin heat sinks under constraints of pressure drop, mass, and space limitations. Khan et al [19,20] studied the thermodynamic losses caused by heat transfer and pressure drop in cylindrical pin fin heat sinks by applying an entropy generation minimization (EGM) technique, which allows all relevant design parameters for pin-fin heat sinks, including geometric parameters, material properties and flow conditions, to be simultaneously optimized. Chiang et al [21,22] explored the optimal values of designing parameters of a pin fin type heat sink under constrains of mass and space limitation to achieve high thermal performance (or cooling efficiency) by experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [20] further found that increasing side/top clearance reduces the dimensionless entropy generation rate. Famouri et al [33] reported the effects of fin size, spacing and tip clearance.…”
Section: Introductionmentioning
confidence: 96%
“…The heat transfer rate experienced a 40% decrease when C/H increases from 0 to 1 at this optimum spacing. Khan et al [20] indicated that the increase in fin tip clearance (0.25 6 C/H 6 1) resulted in an increase in thermal resistance and a decrease in pressure drop for cases with a channel-height-topin-fin-diameter ratio, (C + H)/D, of 12.5. The impact of tip clearance on pressure drop and heat transfer was reported by Moores et al [21].…”
Section: Introductionmentioning
confidence: 98%
“…Такая оптимизация возможна только с применением термодинамического анализа методом минимизации производства энтропии. Работы [12][13][14] принадлежат группе исследователей лаборатории микроэлектро-ники Университета Ватерлоо (Канада). В работах рассмотрена оптимизация компактных оребренных микроканальных охладителей методом минимиза-ции производства энтропии.…”
Section: анализ литературных данных и постановка проблемыunclassified